HARMONIA VOCÁLICA VARIÁVEL NO SISTEMA VERBAL DO PORTUGUÊS DO SUL DO BRASIL - Schwindt, Luiz Carlos; Collischonn, Gisela (Organon, 2004)
This study searches for subsidiary information about the neogrammarian or diffusionistfeatures of Brazilian Portuguese variable vowel raising. This raising, known as vowel harmony, hasreceived neogrammarian (Bisol, 1981) and diffusionist interpretation (Oliveira, 1992). Focalizing onverbs, we reanalize data from Schwindt (1995), a quantitave analyzis of the raising of the pretonicvowels /e/ and /o/ in the samples of Porto Alegre, Florianópolis and Curitiba of the Projeto VARSULcorpus. We restricted investigation to variable /e/ raising in verbs. Data were classified accordingfactor groups referring to verbal classes and morphological boundaries intervening between triggerand target of raising. The VARBRUL program analysis has shown that both verbal classes andmorphological boundaries play a role in raising application. We discuss the implications of thesefindings in relation to the two types of phonological rules.